The study of kerupuk making from casava with pora-pora fish replenishment - Sugito Sugito; Hera Rusmarilin; Linda Masniary Lubis (Jurnal Rekayasa Pangan dan Pertanian, 2013)
This research was conducted to find the concentration of pora-pora fish and concentration of baking powder on the quality of kerupuk. The research had been performed using factorial completely randomized design with two factors, i.e : concentration of pora-pora fish (I) ; 10%, 20%, 30% and 40% and concentration of baking powder (P) ; 0,1%, 0,2%, 0,3% and 0,4%. Parameters analyzed were moisture content, ash content, protein content, fiber content, and organoleptic values (colour, flavor, taste and texture). The results showed that the concentration of pora-pora fish had highly significant effect on moisture content, ash content, protein content, fiber content, and organoleptic values. Concentration of baking powder also had highly significant effect on moisture content, ash content, protein content, fiber content, and organoleptic values. The interaction of the two factors had highly significant effect on moisture content, ash content, protein content, fiber content, and organoleptic values. Concentration of pora-pora fish of 40% and concentration of baking powder of 0,1% produced the best quality of kerupuk. . Key words : baking powder, concentration of pora-pora fish, kerupuk